Historical Pedagogical Content And Characteristics Of Dutor Instrument Performance (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
With the passage of time, the history and unique culture of each nation develops. In particular, the Uzbek people have a rich national culture that is the envy of every nation. In this article, we covered the educational and historical development of dutor, which is a part of our culture, one of our national instruments, performance methods, schools created by master dutor players, based on the scientific research of our musicologists